Competitive advantage through service in hospitality and tourism: a perspective article. Issue 1 (17th November 2019) - Kandampully, Jay; Solnet, David
Abstract : Purpose: Given the dramatic technology led service innovations that are putting pressure on hospitality and tourism businesses, competitive advantage may depend significantly on remaining opportunities for a human element to be incorporated into the customer experience. Design/methodology/approach: This conceptual study provides a synthesis of the past and the future understanding of the importance of service management. Findings: A conceptual framework is provided that extends our understanding of emotion connection and reliance on technology. The examples are given to enrich the discussion. Originality/value: This study is among the first to highlight and explore the interrelationship between emotional connection and the reliance on technology in the context of hospitality experience.